Immunosuppression factors under various pathologies - Ye. G. Churina; V. V. Novitsky; O. I. Urazova (Бюллетень сибирской медицины)
Until recent time it has seemed obvious that suppressive function in the immune system is provided by one subpopulation of Tlymphocytes-suppressors. At present it is usually considered that regulatory cells (T-reg) are key cells-suppressors of the immune response. There exist two main mechanisms of T-reg immunosuppression realization: direct (when there is direct contact between cells) and distant (cytokine-dependent). For suppression of the immune response Т-reg cells produce cytokines with suppression activity: TGF-β, IL-10, IFN-γ, IL-35. Meanwhile the increasing number of facts indicates that suppression of the immune response is a multi-component process. A considerable role in suppression of the immune response is assigned to the endocrine system. However, immunosuppression mechanisms under infection, neoplastic processes and the influence of xenobiotics on the organism are not completely clear.